Kualifikasi Delik dan Pertanggungjawaban Pidana Penipuan Berbasis Deepfake dalam KUHP Nasional - Radhin Naufal Faris; Daniel Sianturi; Taun Taun (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of artificial intelligence has produced deepfake technology capable of convincingly manipulating faces, voices, and videos, creating opportunities for its misuse as a means of fraud. A legal issue arises because Article 492 of Law Number 1 of 2023 concerning the Criminal Code does not specifically regulate deepfake-based fraud, while its application must comply with the principle of legality and the prohibition of analogy. This research aims to examine the interpretation of fraud elements under Article 492 and the construction of criminal liability for parties involved. This normative juridical research employs statutory, conceptual, and case approaches. Legal materials consisting of primary, secondary, and tertiary sources are analyzed qualitatively and prescriptively. The findings indicate that deepfake may constitute a means of deceit when used to mislead victims and induce them to surrender Goods or benefits. Criminal liability is determined according to the role and culpability of each party, while artificial intelligence is positioned as an instrument of the offense.